Sistem Informasi Rekapitulasi Data Penjualan Pada Toko Obat Sinar Raya Berbasis Web - Nurul Khairina; Josua Prayuda Pakpahan (Yayasan Pemimpin Inovasi Science, 2026)
Sinar Raya Drugstore is a pharmaceutical business that still manages sales transactions and drug inventory records manually. This process creates several challenges in data management, including recording inaccuracies, slower report preparation, and limitations in monitoring drug stock effectively. As transaction activities continue to increase, manual data processing becomes less efficient and may affect the accuracy of operational information. To address these issues, this community service program developed a web-based application to support sales and inventory data management through a more organized digital process. The program focuses on developing a Web-Based Sales Data Recapitulation Information System for Sinar Raya Drugstore. The application was implemented using PHP as the programming language and MySQL as the database management system. The development process applied the waterfall method, which consists of requirement analysis, system modeling, application development, evaluation, and maintenance. The implementation results indicate that the developed system is capable of automating transaction recording, generating periodic sales reports, and providing real-time inventory information. In addition, the application helps improve operational efficiency, minimize recording errors, and simplify the process of managing sales data at Sinar Raya Drugstore.